Serum Alanine Aminotransferase Elevations in Survivors of Childhood Cancer: A Report From the St. Jude Lifetime Cohort Study. Issue 1 (25th December 2018) - Green, Daniel M.; Wang, Mingjuan; Krasin, Matthew J.; Srivastava, DeoKumar; Relling, Mary V.; Howell, Carrie R.; Ness, Kirsten K.; Kaste, Sue C.; Greene, William; Jay, Dennis W.; Fernandez‐Pineda, Israel; Pui, Ching‐Hon; et al.
Abstract : The purpose of this study was to define the prevalence of and risk factors for elevated serum alanine aminotransferase (ALT) level among adult childhood cancer survivors (CCS). The study cohort comprised 2, 751 CCS from the St. Jude Lifetime Cohort Study (>10 years postdiagnosis, age ≥18 years). Serum ALT level was graded using the Common Terminology Criteria for Adverse Events v. 4.03. Modified Poisson regression models were used to estimate relative risks and 95% confidence intervals for the association between demographic and clinical factors and grades 1‐4 ALT on the selected models. A total of 1, 339 (48.7%) CCS were female; 2, 271 (82.6%) were non‐Hispanic white. Median age at evaluation was 31.4 years (interquartile range [IQR] = 25.8‐37.8); median elapsed time from diagnosis to evaluation was 23.2 years (IQR = 17.6‐29.7). A total of 1, 137 (41.3%) CSS had ALT > upper limit of normal (Common Terminology Criteria for Adverse Events v. 4.03 grade 1—1, 058 (38.5%); grade 2—56 (2.0%); grade 3—23 (0.8%); grade 4—none). Multivariable models demonstrated non‐Hispanic white race/ethnicity, age at evaluation in years, being overweight or obese, presence of the metabolic syndrome, current treatment with atorvastatin or rosuvastatin or simvastatin, hepatitis C virus infection, prior treatment with busulfan or thioguanine, history of hepatic surgery, and the percentage of liver treated with ≥10 Gray, ≥15 Gray, or ≥20 Gray were associated with elevated ALT. Conclusion: Grade 3 or 4 hepatic injury is infrequent in CCS. Mild hepatic injury in this group may be amenable to lifestyle modifications.